Early elimination of cyclosporine in kidney transplant recipients receiving sirolimus prevents progression of chronic pathologic allograft lesions - Ruiz, JC (2003)
Cyclosporine elimination in a regimen including sirolimus has been shown to be a safe and effective approach to improve graft function. Nevertheless, it is still unknown whether the functional benefit of CyA withdrawal coincides with a subsequent reduction in histologic lesions of chronic damage or development of chronic allograft nephropathy. This consideration would forecast a reduction in the rate of long-term graft loss. We analyzed 114 graft biopsies from a subgroup of 57 patients that had been included in a randomized study to eliminate CyA at 3 months posttransplant from a regimen including sirolimus either in group A CyA + SRL vs group B of SRL with CyA elimination at 3 months. Every patient had two biopsies, one at transplantation and another at 1 year. The biopsy reading was performed in a blinded manner by a central pathologist using the Banff 1997 and the CADI classifications. A significantly lower rate of progression of tubular and interstitial chronic lesions between basal and 1-year biopsies was observed for group B patients. In addition, the incidence of new cases of chronic allograft nephropathy during the first year was significantly lower in the group in which CyA had been eliminated at 3 months posttransplant. We conclude that early elimination of CyA in the first months posttransplant, when SRL is used as the main immunosuppressant, reduces the appearance or worsening of chronic histologic lesions, probably as a consequence of long-term CyA toxicity prevention.